The PERAN PEMERINTAH DALAM MEWUJUDKAN KESEJAHTERAAN RAKYAT : PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE YANG KONSISTEN DAN TERENCANA - Jessica; Ester Nathania Davita Sitanggang; Agustin Widjiastuti; Dave Tedjokusumo (Jurnal Hukum Lex Generalis, 2024)
The system of government in Indonesia has continuously evolved over time, with ongoing efforts aimed at creating a government capable of ensuring the welfare of the Indonesian people. Efforts to achieve a state of welfare include implementing the concept of Good Governance. The principles of Good Governance are fundamental elements in establishing a clean and effective government, free from corruption, with transparent financial flows, and without collusion or nepotism. This research aims to evaluate the effectiveness of applying Good Governance principles and their impact on the welfare of the Indonesian people. The study employs a qualitative research method with a literature review or document analysis approach. This methodology focuses primarily on qualitative analysis of secondary sources, including academic journals, books, and government reports. The literature analysis reveals a consensus on the importance of principles such as transparency, accountability, and participation in enhancing public welfare. Therefore, cooperation between the government and the public is needed to achieve the welfare of the people through Good Governance. The government's role as an agent of change is crucial in implementing the desired reforms. Keywords: People welfare, Goverment’s role,Good governance